Exploring non-medical prescribing for patients with mental illness: a scoping review - Bashayr A Alsaeed; Jason Hall; Richard N. Keers (BMC Psychiatry)
Abstract Background Non-medical prescribing (NMP) qualifications extend prescribing authority to nurses, pharmacists, and other allied health professionals and are advocated as a means to help improve healthcare efficiency and access to services. However, despite non-medical prescribers (NMPs) being utilised in some countries for more than two decades, less is known about their role and impact in the mental health context. This scoping review therefore aims to map published research evidence concerning NMP for patients with mental illness. Methods Five electronic databases were searched from January 2003 to July 2024. Reference lists of identified papers were also checked for relevant studies. Full text primary research studies exploring the nature, impact, and implementation of NMP services for patients with mental illness and dementia in community settings were included. Results From 22,547 retrieved papers, 63 studies were included. Of these, 57 (90.4%) detailed the nature (including the service or team they were based in, medicines prescribed, and main role(s)) of NMPs, 45 (71.4%) assessed the impact of services, and 16 (25.3%) explored factors influencing service implementation and delivery. The majority of studies originated from the USA (30/63, 47.6%), or the United Kingdom (27/63, 42.8%). Either nurse (44/63, 69.8%), pharmacist (16/63, 25.3%) or non-medical prescribing models featuring both professionals were exclusively studied (3/63, 4.7%). In the UK and USA, antidepressants (60%, 54.5%) were the most prescribed by NMPs. Although the conditions of patients managed by both nurse and pharmacist prescribers were reported to be well managed based on clinical outcomes (3/24, 12.5% and 3/13, 23%, respectively), few studies evaluated health outcomes. Training-related barriers to service delivery were commonly mentioned in UK studies (4/9, 44.4%), with financial issues reported in the USA (2/4, 50%). Conclusions This review highlights the diverse roles of NMPs in the care of people with mental illness. Whilst the limited evidence suggests a positive impact on patient care, more quantitative research is needed. Given the focus on nursing prescriber models in this review, along with rising mental health demand and continuing staff shortages, future research should prioritise exploring and evaluating the contribution of pharmacist NMP services as well other healthcare professionals' NMPs.